Studi Daya Dukung Tanah Lempung Lunak yang Distabilisasi Menggunakan TX 300 Sebagai Lapisan Subgrade - Muhammad Jafri; Iswan Iswan; Mirsa Susmarani (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2013)
Road construction requires good subgrade to put down parts of road pavement that it put downabove subgrade. However, soil can make problem if it has bad characteristic and loss, forexample high plasticity, low shear strenght, compression or volume change and large potensial ofswelling-shrinking. To overcome these, it is needed an improvement of soil that is called with soilstabilization use additive and one of them use TX 300 that come from America.Results of laboratory research show stabilization materials use TX 300 as stabilizing agent canimprove the physical and mechanical properties of soft clay soil. On physical test such as specificgravity and plasticity index, it decreased after stabilization. While the mechanical testing, usage ofTX 300 is effective enough in increasing the bearing capacity of soft clay soil. From the testresults of laboratory’s CBR, soil that has been stabilized with a mixture of the TX 300 can be usedas a subgrade for road construction due to CBR’s value ≥ 6 %.